Improving The Ability To Apply Sanitary Pads In A Child With Down Syndrome Through Direct Instruction Learning (Single Subject Research In Grade III At SLB Alisha, Sijunjung Regency) - Yuniarti, Berliana; Mahdi, Arisul; Nurhastuti, Nurhastuti; Yuliana, Syari (Lembaga Riset dan Inovasi Almatani, 2026)
This study was motivated by the low level of self-care ability of a child with Down syndrome in independently performing the skill of applying sanitary pads. Limitations in understanding the sequence of steps, remembering procedures, and coordinating fine motor skills caused the child to remain dependent on assistance from others, especially during menstruation. Based on the results of initial observations and assessments, it was found that the child’s ability to apply sanitary pads was still low and had not been carried out correctly and sequentially. Therefore, a structured, concrete, and repetitive learning model was needed. This study employed an experimental method using a Single Subject Research (SSR) approach with an A–B design consisting of a baseline phase (A) and an intervention phase (B). The research subject was a female third-grade student. Data collection was conducted through performance tests using a task analysis–based assessment instrument. Data were analyzed descriptively using quantitative methods through visual graph analysis, which included within-condition analysis and between-condition analysis. The results of the study showed an improvement in the child’s self-care ability in applying sanitary pads after the implementation of the Direct Instruction learning model. During the baseline phase, the child’s ability was at 58.3% and showed a stable trend. During the intervention phase, the child’s ability increased, reaching the highest percentage of 69.4% and showing a more consistent trend. Based on these results, it can be concluded that the Direct Instruction learning model is sufficiently effective in improving self-care skills in applying sanitary pads for a child with Down syndrome